1993
DOI: 10.1080/00288233.1993.10427486
|View full text |Cite
|
Sign up to set email alerts
|

Introduction, production, and persistence of five grass species in dry hill country

Abstract: (Festuca arundinacea Schreb.), established successfully at most sites. Findlay-Wilkinson analysis of annual total herbage accumulation (THA) of four sites, found that Maru production was above average and resident production was below average. Variation in THA between sites and years was related to variation in annual rainfall (621-1484 mmI year). Wana was the most persistent grass at all sites (60% of THA after 4-6 years), followed by Nui (51 % of THA after 4-6 years). Maru was only persistent at Southland, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
2
12
0
1
Order By: Relevance
“…The first has been the evaluation of alternative pasture species that may have drought resistant characteristics (barker et al 1993;Korte & Rhodes 1993;Fraser et al 1999). These include grasses such as cocksfoot (Dactylis glomerata) as assessed by barker et al (1999), or legumes (macfarlane & Sheath 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The first has been the evaluation of alternative pasture species that may have drought resistant characteristics (barker et al 1993;Korte & Rhodes 1993;Fraser et al 1999). These include grasses such as cocksfoot (Dactylis glomerata) as assessed by barker et al (1999), or legumes (macfarlane & Sheath 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The greater rate of tiller production in Wana and Matua than in Maru is also reported by Barker & Dymock (1993) in North Island hill country. When drilled into dry hill country close to this site, Archie & Vartha (1985) found that the production of Maru relative to Nui and Matua increased over a 3-year period.…”
Section: Climatementioning
confidence: 65%
“…Además, la restricción hídrica reduce la asimilación de carbono y afecta la eficiencia de utilización de nutrientes, siendo el primer factor limitante en la producción de forrajes (Akmal y Janssens, 2004). La limitada precipitación durante el periodo de establecimiento pudo afectar la respuesta en producción de los raigrás evaluados, aunque las producciones de MS fueron similares a las reportadas por Smit et al (2005) y Cuesta (2008, pero menores a las reportadas por Barker et al (1993).…”
Section: Periodo De Producción De Gramíneas Y Leguminosasunclassified